2021
DOI: 10.1016/j.jssr.2021.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Examining Elementary Social Studies Preservice Teachers’ Dispositional Thinking about Museum Pedagogy

Abstract: Evidence is limited on how elementary social studies preservice teachers make sense of museum settings and the use of museum artifacts for instruction, especially while consumed with learning how to teach. This study explored 81 elementary preservice teachers’ dispositional thinking toward museum pedagogy in a teacher education program. Objectives were to determine an overall dispositional thinking profile and also investigate possible distinct dimensions. The study employed descriptive and exploratory factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…First, they stated to lack specific knowledge of and tools for developing instructional practices themselves, resulting from a general lack of training in museum education (Felices-De la Fuente et al, 2021;Görmez, 2020;Uslu, 2020). Resulting from this, PSTs self-assessed their capacities to provide instruction in a museum much lower than their willingness or motivation to visit museums with students (Hubbard & Odebiyi, 2021). Second, PSTs' experiences during their own time as students, being mostly exposed to guided tours when visiting museums, played a considerable role (Felices-De la Fuente et al, 2021).…”
Section: Category 2 Instructional Methods: Between Student-and Teache...mentioning
confidence: 99%
See 2 more Smart Citations
“…First, they stated to lack specific knowledge of and tools for developing instructional practices themselves, resulting from a general lack of training in museum education (Felices-De la Fuente et al, 2021;Görmez, 2020;Uslu, 2020). Resulting from this, PSTs self-assessed their capacities to provide instruction in a museum much lower than their willingness or motivation to visit museums with students (Hubbard & Odebiyi, 2021). Second, PSTs' experiences during their own time as students, being mostly exposed to guided tours when visiting museums, played a considerable role (Felices-De la Fuente et al, 2021).…”
Section: Category 2 Instructional Methods: Between Student-and Teache...mentioning
confidence: 99%
“…Thematically, questionnaires focused on why PSTs would visit history museums with students, what their personal stances towards museum education were and in which way they would incorporate museum visits into the curriculum. Hubbard and Odebiyi (2021) for example aimed to map PSTs dispositional thinking profile towards museum education through an explanatory factor analysis based on a questionnaire. This included their willingness and motivation, their self-perceived capacity and their instructional prospects to incorporate museum visits in social studies lessons.…”
Section: Category 3: Focus On Pre-service Teachers' Beliefs On Visiti...mentioning
confidence: 99%
See 1 more Smart Citation
“…One recent study revealed that museum visits benefit prospective teachers and students from various dimensions [12]. One of the dimensions to foster meaningful museum teaching is through museum pedagogy [13]. A visit to a museum during a teachertraining program can create awareness of museum visits as a pedagogy among trainee teachers [14].…”
Section: Introductionmentioning
confidence: 99%
“…Using primary sources requires important research and critical thinking skills, unlike working with other teaching materials. Museums, which adopt the understanding of contemporary museology, establish museum-school cooperation and establish education departments that will program the education to be carried out by communicating with the society and schools (Hubbard & Odebiyi, 2021). According to the modern understanding of education, the museum a) forces people to think, establishes relationships by making observations, b) teaches people how to improve their knowledge, c) gives them the habit of comparing this information, d) shows the opposites and brings them to a conclusion with a certain interpretation, e) contributes to the formation and development of imagination and sense of taste, observation, creativity and logic, f) reveals the past, compares the past with the present, shows the developments up to the present day, g)…”
Section: Introductionmentioning
confidence: 99%